Enhanced nucleosome assembly at CpG sites containing an extended 5-methylcytosine analogue. Issue 11 (1st June 2022) - Tomkuvienė, Miglė; Meier, Markus; Ikasalaitė, Diana; Wildenauer, Julia; Kairys, Visvaldas; Klimašauskas, Saulius; Manelytė, Laura
Abstract: Methylation of cytosine to 5-methylcytosine (mC) at CpG sites is a prevalent reversible epigenetic mark in vertebrates established by DNA methyltransferases (MTases); the attached methyl groups can alter local structure of DNA and chromatin as well as binding of dedicated proteins. Nucleosome assembly on methylated DNA has been studied extensively, however little is known how the chromatin structure is affected by larger chemical variations in the major groove of DNA. Here, we studied the nucleosome formation in vitro on DNA containing an extended 5mC analog, 5-(6-azidohex-2-ynyl)cytosine (ahyC) installed at biological relevant CpG sites. We found that multiple ahyC residues on 80-Widom and Hsp70 promoter DNA fragments proved compatible with nucleosome assembly. Moreover, unlike mC, ahyC increases the affinity of histones to the DNA, partially altering nucleosome positioning, stability, and the action of chromatin remodelers. Based on molecular dynamics calculations, we suggest that these new features are due to increased DNA flexibility at ahyC-modified sites. Our findings provide new insights into the biophysical behavior of modified DNA and open new ways for directed design of synthetic nucleosomes. Graphical Abstract: